Német-Ausztria születése: 1918. november 12. - Tóth, Imre (Acta Scientiarum Socialium, 2018)
On this November day, politicians and offices of the Austrian state that was being formed since mid-October made their decision on the new provisional constitution. As a result, German-Austria chose republic as the form of state. Therefore, the date is considered to be the birthday of the republic of Austria. In our paper, we present the November 12 events in Vienna and the decisions of the Austrian politicians, thus sketching the birth of German-Austria
Keywords: Great War (1914‒1918); history of Central-Europe; birth of the first Austrian Republic; Vienna